Wood dust and asthma. Issue 2 (6th April 2023) - Baatjies, Roslynn; Chamba, Paulino; Jeebhay, Mohamed F.
Abstract : Purpose of the review: Review recent developments on asthma associated with wood dust, given the increasing scale of wood handling and processing activities globally. Recent findings: Work in wood industries is associated with a significantly increased risk of respiratory symptoms, rhinitis and asthma. This can be attributed to traditional processing techniques and newer technologies producing complex bioaerosol exposures, which may include chemicals. Meta-analysis studies indicate strong evidence for wood dusts as occupational sensitizers for asthma, but the underlying mechanisms remain poorly understood. The global prevalence of asthma in wood workers ranges between 6–18% and for rhinitis 16–33%. Exposure estimates show wide variation. Risk factors include atopy and exposure to certain wood species, elevated current and cumulative particulate exposures. Summary: Future studies should focus on better characterization of wood dust allergens and other bioaerosol components, specific immunoglobulin E responses to different wood species, pathophysiological mechanisms underlying asthma, and modelling dose–response relationships using refined exposure metrics for dust particulate and other bioaerosol components. There is a need for improved health-based international exposure standards and effective workplace control measures to reduce exposures to wood dust particulate (hard and soft woods), endotoxin and β-glucan, to reduce the risks of asthma in wood workers.